Identification and evaluation of risks in the construction and implementation of the II-1 hospital in San Ignacio - Cajamarca - Lizana Adrianzén, Alfredo (2024)
The research identified and assessed the risks in the execution of the construction and implementation project of the San Ignacio II-1 Hospital in Cajamarca in 2022, using the PMBOK Guide as a reference. Fifteen risks were identified, each with three root causes. A survey based on this guide was developed and applied to a population of 50 previously trained project workers. The results showed that 93.33% of the risks were of high or moderate priority. Of the total risks, 6.66% were accepted, 46.67% were avoided, and 46.67% were mitigated. In addition, the prioritisation and response to the risks was linked, determining that 33.33% were remediable, 53.33% tolerable and 13.34% deferable. These findings showed the need for effective risk management strategies to ensure the viability and safety, recommending regular reviews and clear communication to reduce unforeseen events and ensure project success.